Espaço, memória e luta: ativismos e práticas espaciais em Belo Horizonte (1960 a 1983) - Laís Grossi de Oliveira (2023)
The city results from the collective efforts of various agents, classes, and groups. However, the dominant historiography, along with the archives that compile supporting documents, not by chance, continues to prioritize the narratives of a specific subset of individuals: those to whom rights of voice, word, image, and memory have been bestowed. Among those who remain absent and silenced, I seek to historicize the struggles and activism that unfolded in Belo Horizonte and its Metropolitan Region between 1960 and 1983. This analysis is anchored in three key pillars: the struggles themselves (comprising their agendas, modes of organization, and participants); their utilization of space as an integral part of their strategic toolkit; and the historical context within which they unfolded. The aim is to uncover the various ways in which space and activism intersect, seeking to comprehend how and why certain spaces within the capital of Minas Gerais are chosen, as well as specific spatial practices of resistance, valorization, and struggle by indeterminate agents and social groups aiming to amplify their demands. When addressing past activism, including its strategies for appropriating space and the associated meanings, the primary challenge arises from its invisibility or omission within official historiography. Therefore, the archives of the DOPS/MG Fund and the Minas Gerais State Secretariat for Public Security Fund SESP/MG serve as initial reference points. In addition, we integrated reports compiled by fellow researchers, as well as the biographies or autobiographies of activists or groups that were active during the analysis period, into these narratives. Consequently, the intention is to create connections and rectify the historiography of Belo Horizonte and the Metropolitan Region, drawing upon the historical recovery of their struggles and activism by an indeterminate collective.